2022
DOI: 10.3389/fmicb.2022.1062515
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation quality, bacterial community, and predicted functional profiles in silage prepared with alfalfa, perennial ryegrass and their mixture in the karst region

Abstract: There is little information regarding the dynamics of fermentation products and the bacterial community in silage prepared with alfalfa (MS), perennial ryegrass (LP), and their mixture in the karst region. In this study, we explored the effects of combining MS with LP in different ratios (100% MS, 70% MS + 30% LP, 50% MS + 50% LP, 30% MS + 70% LP and 100% LP; fresh matter basis) on silage chemical composition, fermentation quality, bacterial communities and predicted functions during the ensiling process. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The metabolic pathways were specifically analyzed at the third level. The relative abundances of "biosynthesis of secondary metabolites" and "biosynthesis of antibiotics" in the FA and LAB groups were greater than those in the CK group after 7 and 45 days of ensiling, and similar results were found in the study of Fan et al [14]. The relative abundances of "ABC transporters" in the FA group after 7 days of ensiling and in the FA and LAB groups after 45 days of ensiling were lower than those in the CK group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The metabolic pathways were specifically analyzed at the third level. The relative abundances of "biosynthesis of secondary metabolites" and "biosynthesis of antibiotics" in the FA and LAB groups were greater than those in the CK group after 7 and 45 days of ensiling, and similar results were found in the study of Fan et al [14]. The relative abundances of "ABC transporters" in the FA group after 7 days of ensiling and in the FA and LAB groups after 45 days of ensiling were lower than those in the CK group.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, ensiling AL with PR might be a useful technique for enhancing the nutritional value and fermentation quality of silage. However, even though our previous studies showed that the nutritional quality of mixed silage ensiled with AL and PR improved, the fermentation quality was not satisfactory (pH 4.63-5.94) [14]. Hence, according to previous studies, silage additives are required to further improve the fermentation quality of mixed silage ensiled with AL and PR.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Generally, NH 3 -N accumulates continuously during fermentation ( Dong et al, 2022a ). When LAB dominated in the late stages of ensiling, lactic acid was produced by the fermentation of plant biomass and the pH was reduced to a level that inhibited the activity of ammonia nitrogen producing bacteria ( Fan et al, 2022 ). This could explain the correlation between pH and the NH 3 -N:TN ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in DM and carbohydrates is due to the metabolic activity of lactobacilli during fermentation. These microorganisms convert nutrients into organic acids, ethanol, and other metabolic products [21,22].…”
Section: Discussionmentioning
confidence: 99%